Are there better methods of monitoring MRSA control than bacteraemia surveillance? An observational database study - Walker, S; Peto, T; O'Connor, L; Crook, D; Wyllie, D (Public Library of Science, 2008)
Background: Despite a substantial burden of non-bacteraemic methicillin resistant Staphylococcus aureus (MRSA) disease, most MRSA surveillance schemes are based on bacteraemias. Using bacteraemia as an outcome, trends at hospital level are difficult to discern, due to random variation. We investigated rates of nosocomial bacteraemic and non-bacteraemic MRSA infection as surveillance outcomes. Methods and Findings: We used microbiology and patient administration system data from an Oxford hospital to estimate monthly rates of first nosocomial MRSA bacteraemia, and nosocomial MRSA isolation from blood/respiratory/sterile site specimens (‘‘sterile sites’’) or all clinical samples (screens excluded) in all patients admitted from the community for at least 2 days between April 1998 and June 2006. During this period there were 441 nosocomial MRSA bacteraemias, 1464 MRSA isolations from sterile sites, and 3450 isolations from clinical specimens (8% blood, 15% sterile site, 10% respiratory, 59% surface swabs, 8% urine) in over 2.6 million patient-days. The ratio of bacteraemias to sterile site and all clinical isolations was similar over this period (around 3 and 8-fold lower respectively), during which rates of nosocomial MRSA bacteraemia increased by 27% per year to July 2003 before decreasing by 18% per year thereafter (heterogeneity p < 0.001). Trends in sterile site and all clinical isolations were similar. Notably, a change in rate of all clinical MRSA isolations in December 2002 could first be detected with conventional statistical significance by August 2003 (p = 0.03). In contrast, when monitoring MRSA bacteraemia, identification of probable changes in trend took longer, first achieving p < 0.05 in July 2004. Conclusions: MRSA isolation from all sites of suspected infection, including bacteraemic and non-bacteraemic isolation, is a potential new surveillance method for MRSA control. It occurs about 8 times more frequently than bacteraemia, allowing robust statistical determination of changing rates over substantially shorter times or smaller areas than using bacteraemia as an outcome.